2016
DOI: 10.1186/s13059-016-1096-8
|View full text |Cite
|
Sign up to set email alerts
|

TET-dependent regulation of retrotransposable elements in mouse embryonic stem cells

Abstract: BackgroundTen-eleven translocation (TET) enzymes oxidise DNA methylation as part of an active demethylation pathway. Despite extensive research into the role of TETs in genome regulation, little is known about their effect on transposable elements (TEs), which make up nearly half of the mouse and human genomes. Epigenetic mechanisms controlling TEs have the potential to affect their mobility and to drive the co-adoption of TEs for the benefit of the host.ResultsWe performed a detailed investigation of the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 64 publications
6
77
0
Order By: Relevance
“…Noting that the field lacked a comprehensive analysis of TET interaction with TE sequences, de la Rica and colleagues [4] mined ChIP-seq data to determine the distribution of TET1 peaks at distinct TE classes. Their analysis revealed significant enrichment of TET1 at L1s and several types of LTR retrotransposons, suggesting that TET1 may have a widespread role in TE regulation.…”
Section: Tet Enzymes—multiplayers In Te Regulationmentioning
confidence: 99%
See 4 more Smart Citations
“…Noting that the field lacked a comprehensive analysis of TET interaction with TE sequences, de la Rica and colleagues [4] mined ChIP-seq data to determine the distribution of TET1 peaks at distinct TE classes. Their analysis revealed significant enrichment of TET1 at L1s and several types of LTR retrotransposons, suggesting that TET1 may have a widespread role in TE regulation.…”
Section: Tet Enzymes—multiplayers In Te Regulationmentioning
confidence: 99%
“…De la Rica and colleagues [4] also observed that TET1 peaks at LTR elements were associated with active enhancer marks, as well as the pluripotency factors NANOG, OCT4, and SOX2 (collectively referred to as NOS). This observation is consistent with the occupied TE sequences acting as enhancers, and led to the hypothesis that TET proteins have a role in TE-derived enhancer function, important for ESC gene expression networks.…”
Section: Tet Enzymes—multiplayers In Te Regulationmentioning
confidence: 99%
See 3 more Smart Citations